Impact Of Fragrant Pandan Leaves Ethanol Extract (Fplee) On Alt And Ast Levels In High-Fat Diet-Induced Rat - Sukanty, Ni Made Wiasty; Ariani, Farida; Yunita, Lina (Jurnal Riset Kesehatan, 2024)
Energy-dense, low-nutrient, and ultra-processed diets rich in fat can be a risk factor for fatty liver disease. Fragrant pandan is a plant that grows widely in Indonesia and is widely used as a herbal plant. This study aimed to determine the potential of fragrant pandan leaf ethanol extract (FPLEE) to reduce ALT and AST levels. It is a posttest control group design experiment. A total of 24 Rattus norvegicus specimens. All groups were given high-fat food for two weeks, except for NC. In the next two weeks, S was induced by simvastatin and FPLEE; T1, T2, and T3 were induced by 8, 16, and 32 mg/200 g BW/day, respectively. The One-Way ANOVA test results showed α=0.000 for ALT and α=0.029 for AST. Post-hoc LSD showed that NC was significantly different from T1, T2, and T3 (p0.05); therefore, FPLEE was unable to reduce ALT levels. For AST levels, NC was significantly different from C+, T1, and T2 (P0.05). Thus, T3 (32 mg/200 g BW/day of FPLEE) yielded the best results in reducing AST levels (p0.05). Based on these results, FPLEE has side effects on liver function, as seen in increased blood ALT levels, but it can reduce blood AST levels.